New insight into residual stresses in amine-grafted MWCNTs/binary resin composites under complex thermomechanical loadings. (November 2019) - Wang, Junxia; Chen, Xiaochuan; Cao, Changlin; Yu, Dingshan; Yan, Shilin
Herein, we detailed the distributions and distortions of residual stresses in amine-grafted multiwalled carbon nanotubes (MWCNTs)/binary resin composites under complex thermomechanical loadings suffered in practical processing or operation, by means of finite element simulation. First, distributions and distortions of residual stresses under coupled extensional–shear loadings were studied. Subsequently, thermal residual stresses were deducted from the thermal analysis, followed by a sequentially structural analysis. It is found that the heat flux has an influence on the magnitude of the thermal residual stresses, but it cannot alter the distribution of the thermal residual stresses. In order to render deep understanding of the microscale behavior in amine-grafted MWCNTs/binary resin composites under thermal loading, for exploring the nature of residual stress variation, the corresponding microscale model is expected to be developed using atomistic simulation, in which the microstructural features of amine-grafted MWCNTs and resin matrix are taken into consideration. The total energy, potential energy, and kinetic energy at different temperature were analyzed as well as the radial distribution function g ( r ). Weak van der Waals interaction between amine-grafted MWCNTs and resin matrix is indicated and the interactions between amine-grafted MWCNTs and resin matrix reduce and the mobility of chain segments of resin matrix increases with the decreasing temperature.